Is There a Swan in this Poem? Yeats and Symbolist Poetics - Potolsky, Matthew (Miscelánea: A Journal of English and American Studies, 1999)
Although the poetry of W. B. Yeats has long been associated with the imagery and ideals of French symbolism, it is assumed that Yeats turns away from symbolism in the twentieth century and endorses a more public, if still hermetic, model of poetry. While this story may be true for Yeats's poetic imagery, Yeats continues to draw upon symbolist techniques of poetic "decomposition", even where such techniques seem not to be in evidence. Comparing two famous swan poems -Mallarme's "Le vierge, le vivace, et le bel aujourd'hui" and Yeats's "The Wild Swans at Coole"- this paper argues that Yeats continues to draw upon symbolist methods even after he claims to have rejected them. Both poems generate a' tension between the represented scene described by the lyric voice and the linguistic or allegorical resonances of the poem's language. And in both poems this tension works to "decompose" the scene. Where Mallarme effects this decomposition through the material qualities of his language, Yeats presents a landscape that can be read both mimetically (as a place the poet sees) and allegorically (as an embodiment of a system of symbolic correspondences).